1999
DOI: 10.1046/j.1365-2222.1999.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous air pollution and atopy

Abstract: The increase in photochemical air pollutants is unlikely to be a major determinant for the recent increase in the prevalence of atopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 17 publications
1
22
2
Order By: Relevance
“…We have recently reported an increase in the proportion of positive cutaneous IgE-mediated responses in 234 traffic wardens with a well defined occupational history of road traffic fume exposure in the city of Catania which has one of the highest levels of traffic intensity in Italy (60). In contrast, such differences were not observed in other studies (61,62). However these studies refer exclusively to gaseous air pollution and not to particulate pollutants; there is no experimental evidence that gaseous air pollutants are able to enhance IgE production or atopic sensitization.…”
mentioning
confidence: 72%
“…We have recently reported an increase in the proportion of positive cutaneous IgE-mediated responses in 234 traffic wardens with a well defined occupational history of road traffic fume exposure in the city of Catania which has one of the highest levels of traffic intensity in Italy (60). In contrast, such differences were not observed in other studies (61,62). However these studies refer exclusively to gaseous air pollution and not to particulate pollutants; there is no experimental evidence that gaseous air pollutants are able to enhance IgE production or atopic sensitization.…”
mentioning
confidence: 72%
“…Although mean levels of each pollutant (sulfur dioxide, nitrogen dioxide, and ozone) differed between towns, there was no correlation between the level of air pollution, the presence of atopy in children, and the level of dust mite allergen in the mattresses of sensitized children. Therefore, this study did not demonstrate an association between higher air pollution levels and atopic status, although a major limitation was that it only measured outdoor ambient air pollutant levels rather than personal exposure [18].…”
Section: Atopymentioning
confidence: 90%
“…For example, a study conducted in France that measured the air pollutants sulfur dioxide, nitrogen dioxide, and ozone over a 2-month period at various monitoring stations in a region known to have the highest level of air pollution in France found no association with sensitization [18]. In this study, parents of 2604 students were asked to answer a health questionnaire about their children, and all children who had not been previously skin tested or who were not undergoing desensitization (n = 2073) were skin prick tested to fi ve standardized allergen extracts.…”
Section: Atopymentioning
confidence: 99%
“…Exposure to ambient air pollutants has been suggested to increase the risk of AR in children, but the evidence was still weak and inconclusive [6][7][8][9][10][11][12][13]. Some studies have suggested that exposure to outdoor air pollutants, especially for traffic-related pollutant, may increase the risk of allergic rhinitis in children [6][7][8].…”
mentioning
confidence: 99%